On strikes with respect to hours of labour - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1865)
In old times, when business of all kinds was carried on in small establishments, the hours of labour were regulated by the hours kept by the employer and his family, who generally resided at the place of business, and personally superintended the work. The old hours in all common occupations were ten hours for work, with two hours for meals, twelve in all?usually from six a.m. to six p.m. When capitalists get up large establishments like factories, and have a large capital sunk in machinery, they are tempted to make the machinery work as many hours as possible out of the twenty-four. The capitalist is thus led to offer extra wages for extra hours, to induce the men to overwork; and not the men only, but women and children. It was to check this evil that the agitation for Factory Legislation commenced.
Read Tuesday, 25th September, 1865
Keywords: Factory legislation; Hours of labour; Factory Act; Labour strikes; 314.15